Knowledge and indifference in English Romantic prose - Milnes, Tim (Cambridge University, 2013)
This ambitious study sheds new light on the way in which the English Romantics dealt with the basic problems of knowledge. Milnes argues that it is in their oscillation between knowledge and indifference that the Romantics prefigure the ambivalent negotiations of modern post-analytic philosophy.